DETERMINANTS OF ISLAMIC DEPOSIT CUSTOMER 'S BEHAVIOR: RELIGIOSITY, SERVICE, TRUST, BENEFITS, AND TECHNOLOGY - Arif Mahendra; Muhammad Muflih; Sumiyati (JAT : Journal Of Accounting and Tax, 2026)
Third ‑party funds (DPK) in Indonesia's Islamic banking sector have grown significantly, yet their market share remains relatively small compared to conventional banks, highlighting a persistent gap between religious commitment and actual saving behavior among Muslim customer. Previous studies have predominantly focused on behavioral intention, customer loyalty, or satisfaction, while limited attention has been given to actual deposit behavior. This study this gap by examining the effects of financial religiosity, Islamic service quality, trust in DPK products, perceived benefits of DPK, and Islamic banking information technology on actual DPK customer behavior, conceptualized as continuous depositing, non-switching, and advocacy. A quantitative explanatory cross-sectional survey was conducted on 255 customers of Sharia Commercial Bank (BUS) in greater Bandung using a five-point Likert-scale questionnaire. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that financial religiosity, perceived benefits, and Islamic banking information technology significantly influence DPK customer behavior, while Islamic service quality and trust do not show significant effects. Perceived benefits emerge as the most dominant determinant, confirming that economic rationality remains central even within religious financial decision-making. The model explains 80.3% of the variance in customer behavior. Theoretically, this study extends depositor behavior literature by shifting the focus from behavioral intention to actual behavior and integrating religious, economic, relational, and technological determinants in one model. Practically, the findings provide strategic insights for Islamic banks to strengthen deposit mobilization and retention.